Buddhist studies in the west, past and present: Role of the Mongolian Buddhism - B, Sainbileg (Proceedings of the Mongolian Academy of Sciences, 2018)
In this article, I tried to illustrate a brief history of Buddhist Studies in the Western world and role of Mongolian Buddhism in its history and future prospects. Buddhist Studies is an independent academic discipline that pioneered by outstanding Western scholars and it covers roughly 200 years. In the modern world, Buddhist Studies has formed interdisciplinary academic research, and expands its research area with new requirements of society and newly discovered manuscripts. From the outset of the Buddhist Studies, western scholars involved with Mongolian Buddhism and manuscripts; however, unfortunately Buddhist Studies in the Mongolian context could not develop in parallel with its rapid development. In other words, Mongolian Buddhism comparatively has been slighted in the past history of Buddhist Studies. The researches by domestic scholars have been reviving after 1960. Only foreign scholars do conspicuous researches on the Mongolian Buddhism, but domestic scholars are not active on the academic research due to some reasons. First of all we should define what makes Buddhism “Mongolian”. We should describe identity of the Mongolian Buddhism, and then we able to analyze its past, present and future prospects. I assume the following five tendencies explore researches of the Mongolian Buddhism. Assimilation of Buddhism with Mongolian tradition and customs, syncretism of Buddhism and Mongolian traditional shamanism Distinctive character of Mongolian monasticism, secularity, role of Buddhism in the Mongolian society Study of ethnic Mongolian lamas as influential historical figures Research of Mongolian Canons and other sources in Mongolian language, and their translation Study on Tibetan and Mongolian works by Mongolian lamas in comparison with doctrinally affiliated works